Synthesis and Evaluation of the 2-Aminothiazoles as Anti-Tubercular Agents - Kesicki, Edward A.; Bailey, Mai A.; Ovechkina, Yulia; Early, Julie V.; Alling, Torey; Bowman, Julie; Zuniga, Edison S.; Dalai, Suryakanta; Kumar, Naresh; Masquelin, Thierry; Hipskind, Philip A.; Odingo, Joshua O.; et al. (PLOS ONE, 2016)
The 2-aminothiazole series has anti-bacterial activity against the important global pathogen Mycobacterium tuberculosis. We explored the nature of the activity by designing and synthesizing a large number of analogs and testing these for activity against M. tuberculosis, as well as eukaryotic cells. We determined that the C-2 position of the thiazole can accommodate a range of lipophilic substitutions, while both the C-4 position and the thiazole core are sensitive to change. The series has good activity against M. tuberculosis growth with sub-micromolar minimum inhibitory concentrations being achieved. A representative analog was selective for mycobacterial species over other bacteria and was rapidly bactericidal against replicating M. tuberculosis. The mode of action does not appear to involve iron chelation. We conclude that this series has potential for further development as novel anti-tubercular agents.